(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
After the LPG (liberalization, privatization and globalization) policyin 1991, the Government of India had tried to bring many reforms in thefinancial sector of Indian market. The prime objectives behind these reformswere to make the Indian capital market up to the international standard,improve profitability, improve the legal scenario of capital market, lesser theunfair trade practices and enhance transparency. Many reforms took place likeone-line trading in exchanges, opening stock market to foreign investors etc.Among all these reforms a major reform took place in June 2000 in Indianfinancial market as, at this time period the derivatives introduced in theIndian financial market at two major stock exchanges i.e. BSE & NSE. Due tointroduction of derivatives, the Indian cash market got swayed. Derivativemarket has shown a Marvelous growth both in terms of volume and number oftraded contracts. The present study attempts to discuss the impact of launch ofderivatives on cash market and the correlation between the cash segment andderivative segment. A special focus is given to stock index future because itseems to be more dominant in the derivative market. The data has been analyzedby using regression and correlation. This study concludes that the cash marketis dependent on the derivative market and both the markets are highlycorrelated.